If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-234=6(-6x+3)
We move all terms to the left:
-234-(6(-6x+3))=0
We calculate terms in parentheses: -(6(-6x+3)), so:We get rid of parentheses
6(-6x+3)
We multiply parentheses
-36x+18
Back to the equation:
-(-36x+18)
36x-18-234=0
We add all the numbers together, and all the variables
36x-252=0
We move all terms containing x to the left, all other terms to the right
36x=252
x=252/36
x=7
| -6=-8(1a+4)+8a | | w-1.3=9.8 | | -8-1x=1x—4 | | -6=-8a+-32+8a | | 3|x+9|=6x | | 1/5(x-2)=110(x+6) | | -6(2x+10)=24 | | v+1.24=3.95 | | 4/3(c−3)=3/8(3c+6) | | V^2-4v-32=8 | | -8n+4(1+5n)=-6n-145 | | 20=2/5v | | (6x+5)+(4x+15)=120 | | 43(c−3)=38(3c+6) | | 67=11h+1 | | 67=11h-1 | | 1/2x+3/4=1/4 | | 7/4y=21 | | 6x+5+4x+15=180 | | 3(n+2)=9(6–n) | | .5(4x-10)=-7 | | 35-x=13x | | 3x+8=7(x+4) | | (6x+5)+(4x+15)=0 | | 3(x-19)=75 | | v+2.93=7.88 | | 3(x-19)=51 | | 2a+9=a+11 | | (4x+15)+(6x+5)=180 | | 9.50p=13.50 | | -2(j-3=-2j+6 | | -3(2x+3)=-3 |